2023
DOI: 10.3390/foods12020405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yogurt Enrichment with Wood Tannin during Shelf Life: Focus on Physicochemical, Microbiological, and Sensory Characteristics

Abstract: Six food-grade tannins obtained from different woods were used as a source of polyphenolic compounds at two concentrations (0.5% and 1% w/w) in yogurt formulations and monitored during 3 weeks of storage. Yogurt containing tannins showed significantly higher total phenolic content (+200%), antioxidant activity (+400%), and syneresis (+100%) than control. These changes were higher with fortification at 1%. Tannin origin also significantly influenced the yogurt composition and yogurt obtained from a Turkish gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recent studies, such as that by Zadeh et al ( 54 ), have shown that the addition of tannins to yoghurt does not significantly affect the number of lactic acid bacteria, but may influence consumer acceptability. The preference for tannins varies according to their origin, with a higher preference observed for tannins from quebracho wood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, such as that by Zadeh et al ( 54 ), have shown that the addition of tannins to yoghurt does not significantly affect the number of lactic acid bacteria, but may influence consumer acceptability. The preference for tannins varies according to their origin, with a higher preference observed for tannins from quebracho wood.…”
Section: Resultsmentioning
confidence: 99%
“…The preference for tannins varies according to their origin, with a higher preference observed for tannins from quebracho wood. In addition, Ibrahim et al ( 55 ) have shown that the use of tannin-free pomegranate peels can improve the viability of probiotic cultures in yoghurt ( 54 ). Further studies by Lee et al ( 51 ) and Barakat and Hassan ( 49 ) have shown that the addition of ginseng or pumpkin pulp extracts to yoghurt can affect sensory properties such as colour, taste and overall acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…Dairy products are a fertile field in terms of the possibility of developing them by integrating many available added-value ingredients with milk products, such as yogurt. Yogurt is already considered a healthy food because it contains viable bacteria but does not contain dietary fiber compounds [ 11 , 12 ]. Yogurt is an exceedingly consumed dairy food globally, renowned for its health benefits, nutritional value, and digestibility [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Applications of tannins in the food sector are increasing, driven by the evidence of their biological value and the market demand for functional and healthier products [14][15][16][17]. In addition to the long-practiced use of tannins in wine, beer and spirits manufacturing for the improvement of taste, clari cation and antioxidant properties, their use as ingredients or additives in the food industry is still limited, however with growth potential especially with regards to the antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%